2005
DOI: 10.3138/jvme.32.2.182
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Stress Factors for Veterinary Medical Students

Abstract: Psychological distress has been shown to affect the academic success, health, emotional well-being, and dropout rates of medical students. Although it can be assumed that stress has similar effects on veterinary students, there is a paucity of research pertaining to the psychological stressors and coping strategies of this group. This article focuses on selected non-academic areas (as identified through a survey of currently enrolled students) that can create significant stressors for veterinary students. Also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 15 publications
3
37
2
1
Order By: Relevance
“…Some studies have shown to indicate that the low quality of life among students can lead to the decreased mental capacity (Sukharev and Mikhaĭlova 2004), psychological distress (Strand et al 2005) and depression. Therefore, QOL, its protection, promotion and development among these groups of people should be emphasised with great importance.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Some studies have shown to indicate that the low quality of life among students can lead to the decreased mental capacity (Sukharev and Mikhaĭlova 2004), psychological distress (Strand et al 2005) and depression. Therefore, QOL, its protection, promotion and development among these groups of people should be emphasised with great importance.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, students' mental and general health ratings, socio-demographic characteristics, psychological symptoms, and experience of stressors were all linked to their academic achievement (Vaez and Laflamme 2008). Although it can be assumed that stress mediate students' QOL and health, there is a paucity of research pertaining to the coping strategies of this social group (Strand et al 2005). In similar tone, psychological variables that will be described below such as sense of coherence (SOC), self-efficacy (SE), level of optimism (LOO) can be regarded as the coping strategies among students and social ones such as social background and type of faculty may influence their quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…11,16,24 When we compared stress levels with another study involving pharmacy students 4 , our students' stress levels were lower whereas they were higher when compared to veterinary students. 25 The mean total stress scores for our study were significantly lower than the normalized mean of 50.…”
mentioning
confidence: 85%
“…Powers 11 found that while students reported certain stressors associated with studying veterinary medicine, they did not feel inordinately stressed and were positive about their veterinary school experience. Another study found that veterinary students did not experience excessive stress, but did report greater levels of subjective stress 6 . However, as these studies involved single populations and did not directly compare with other student groups, it is unclear whether the experiences and mental health of veterinary students differ from those of other similar student populations.…”
Section: Introductionmentioning
confidence: 99%
“…Studies using validated psychological scales have shown that UK and US veterinary students experience lower levels of wellbeing and poorer mental health than the general population [3][4][5][6] . Factors contributing to stress among US and Australian veterinary students include heavy workloads, academic worries, time pressures, work-life balance and concerns about the responsibilities of professional practice [7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%